(untitled) (Research, Society and Development, 2025)
Biotechnology has been consolidated as one of the main pillars of innovation in Brazilian agriculture, combining productivity gains with sustainable practices and reduced environmental impact. This article aims to conduct a narrative review on the advances, applicability, and perspectives of biotechnology in agriculture, with a focus on the Brazilian scenario. The methodology consisted of a narrative review carried out in databases such as Google Scholar, Web of Science, and Scopus, covering the period from 2018 to 2025. The results show that Brazil occupies a leading global position in the adoption of genetically modified crops, especially soybean, corn, and cotton, as well as in the rapid expansion of bioinput use. Among the main advances are biological nitrogen fixation and the development of beneficial microorganisms capable of improving nutrient uptake and strengthening plant resistance. New biotechnologies, such as gene editing with CRISPR-Cas9, emerge as promising alternatives to create more resilient cultivars. The review also highlights challenges, such as the need for continuous research investment, the establishment of clear regulatory frameworks, and the expansion of social acceptance. It is concluded that biotechnology in Brazilian agriculture is configured not only as an instrument of economic growth but also as a strategic pathway to ensure food security and preserve natural resources, consolidating the country as a global reference in sustainable agriculture.